Separation during the construction of bridge crossings use of modern technologies in the performance of work - Kusainova, Гульнар; Tanat, Найля (Рroblems of engineering and professional education, 2023)
This article describes the performed geodetic works during the construction of the bridge. The article purpose to give an overview of the use of modern surveying instruments with location survey in the construction of bridges by examples, as is currently in the construction of bridges and bridge crossings are increasingly common problem is lack of information about the usage of instruments by professionals. In an article in the form of diagrams and drawings presented a detailed description of reference grids, the example of usage of laser levels while stakeout of bridge bearings. There are advantages of the use of modern equipment at the stakeout works of construction of the bridge. The given data of standard deviation allowed while stakeout.